Agglutinin chip screening of B cell surface biomarkers in Hashimoto’s thyroiditis for therapeutic targeting - Ren, Jun-ling; Wang, Xiao-ming (Frontiers in Immunology, 2025)
Background and objectivesHashimoto's thyroiditis (HT) is a chronic autoimmune thyroid disorder characterized by B lymphocyte dysregulation and the production of autoantibodies. This study aimed to evaluate a targeted B cell depletion strategy by identifying and validating a disease-associated membrane glycoprotein selectively expressed on B cells.MethodsB lymphocytes were isolated from peripheral blood samples of 32 individuals with HT and 40 age- and sex-matched healthy controls (HC). Membrane glycoprotein expression was profiled using a 38-lectin microarray, followed by differential analysis via liquid chromatography-tandem mass spectrometry. Tetraspanin-33 (TSPAN33) was identified for further investigation based on its expression pattern. Recombinant TSPAN33 protein was used as the target in a Systematic Evolution of Ligands by Exponential Enrichment (SELEX) process to generate high-affinity DNA aptamers. This aptamer was chemically conjugated with a CD20 monoclonal antibody (rituximab) using bismaleimide crosslinking to generate a bispecific complex with capable of specific binding pathogenic B lymphocytes. Binding specificity was evaluated using confocal microscopy.ResultsThe fluorescence intensity of cell membrane glycoproteins and plasma glycoproteins corresponding to lectins MAL-II and PHA-E was significantly higher in HT patients than in HC patients. The cell membrane protein TSPAN33 bound by the above two lectins is highly expressed in HT patients. The binding energy of aptamer 40 (AP40) to TSPAN33 was 33.2510-9M. AP40 could bind specifically to B cells derived from BALL-1, but not to B cells derived from HC. AP40 can be conjugated with rituximab and purified.ConclusionThe development of a bispecific aptamerantibody conjugate targeting TSPAN33 offers a promising strategy for selective B cell depletion.